An Elastoplastic Constitutive Model for Porous Materials - Huang, Zhuping; Yongqiang Chen; Bai, Shu-Lin (International Journal of Applied MechanicsInternational Journal of Applied MechanicsInternational Journal of Applied Mechanics, 2013)
A micromechanics-based elastoplastic constitutive model for porous materials is proposed. With an assumption of modified three-dimensional Ramberg-Osgood equation for the compressible matrix material, the variational principle based on a linear comparison composite is applied to study the effective mechanical properties of the porous materials. Analytical expressions of elastoplastic constitutive relations are derived by means of micromechanics principles and homogenization procedures. It is demonstrated that the derived expressions do not involve any additional material constants to be fitted with experimental data. The model can be useful in the prediction of mechanical properties of elastoplastic porous solids.
Keywords: constitutive relation; law; micromechanics; modified ramberg-osgood equation; nonlinear composites; plasticity; Porous materials; potentials; reinforced composites; solids; variational principle